Nonlinear Stability Analysis of Imperfect Three-phase Sandwich Laminated Polymer Nanocomposite Panels Resting on Elastic Foundations in Thermal Environments - Thu, Pham Van; Duc, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics; Vol 32 No 1, 2016)
Abstract: In this paper, the problem of nonlinear stability response of imperfect three-phase sandwich laminated polymer nanocomposite panels resting on elastic foundations in thermal environments is investigated using an analytical approach. Governing equations are derived based on classical shell theory, incorporating von Karman–Donnell type nonlinearity, initial geometrical imperfection, and Pasternak type elastic foundations. By applying the Galerkin method, an explicit expression to find the critical load and post-buckling load-deflection curves are obtained. The effects of fibres and nano-particles, material and geometrical properties, foundation stiffness, imperfection, and temperature on the buckling and post-buckling loading capacity of the three-phase sandwich laminated composite panel are analysed. Keywords: Nonlinear stability analysis, three-phase sandwich laminated polymer nanocomposite panel, thermal environments, imperfection, elastic foundations